2012
DOI: 10.1007/s00204-012-0849-8
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates gentamicin-induced nephrotoxicity and oxidative stress in rats

Abstract: The present study investigated the protective effects of melatonin (MT) against gentamicin (GM)-induced nephrotoxicity and oxidative stress in rats. We also investigated the effects of MT on induction of apoptotic cell death and its potential mechanisms in renal tissues in response to GM treatment. The following four experimental groups were evaluated: (1) vehicle control, (2) MT (15 mg/kg/day), (3) GM (100 mg/kg/day), and (4) GM&MT. GM caused severe nephrotoxicity as evidenced by increased serum blood urea ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 48 publications
3
43
0
1
Order By: Relevance
“…In conjunction with findings in the current study, authors have reported the ameliorative effect of NAC in human and animal models of drug associated renal toxicity .52-55 Also, MT have been reported to mitigate various forms of xenobioticinduced renal toxicity in animal models. [56][57][58][59][60] The observed decreases in serum levels of creatinine, urea and uric acid in MT and NAC pretreated rats could be attributed to their inhibitory effects on free radical-induced kidney damage and renal vasoconstriction. Studies have shown that treatment with NAC ameliorate decline in glomerular filtration rate and stabilized plasma creatinine by reducing vasoconstriction.…”
Section: Discussionmentioning
confidence: 94%
“…In conjunction with findings in the current study, authors have reported the ameliorative effect of NAC in human and animal models of drug associated renal toxicity .52-55 Also, MT have been reported to mitigate various forms of xenobioticinduced renal toxicity in animal models. [56][57][58][59][60] The observed decreases in serum levels of creatinine, urea and uric acid in MT and NAC pretreated rats could be attributed to their inhibitory effects on free radical-induced kidney damage and renal vasoconstriction. Studies have shown that treatment with NAC ameliorate decline in glomerular filtration rate and stabilized plasma creatinine by reducing vasoconstriction.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, melatonin can inhibit the catalytic activity of nitric oxide synthase (NOS) and expression of inducible nitric oxide synthase (iNOS) at the transcriptional level that reduces the amount of NO produced. 27 Besides direct scavenger activity, melatonin can stimulate gene expression and activities of several antioxidative enzymes including GRd, GPX, CAT, and SOD, and this indirect antioxidant activity of melatonin is related to its interaction with either membrane or nuclear receptors. These antioxidative enzymes can metabolize free radicals to less reactive species and thereby decrease the formation of highly toxic by-products.…”
Section: Discussionmentioning
confidence: 99%
“…proximal tubular cells as the possible mechanism through which gingerol and other antioxidant substances ameliorate GM-induced nephrotoxicity. Other substances with antioxidant properties have been tested in aminoglycoside-induced nephrotoxicity (42)(43)(44). In the present study, we used a model that approximates clinical practice: an in vivo study, protective substance administration initiated after the use of the toxic agent, and evaluation of functional parameters with clinical relevance (e.g., CL CR ), in addition to histopathology, inflammatory gene expression, and oxidative status.…”
Section: Figmentioning
confidence: 99%